Growth Pattern and Survival of Mangrove Seedlings on the Coast of Peunaga Cut Ujong, West Aceh - Lisdayanti, Eka; Najmi, Nurul; Rahmawati; Hermawan, Eko Perbowo Dian (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Mangroves are coastal ecosystems with different abilities to adapt to changing environmental conditions. Habitat characteristics that continue to change cause morphological, anatomical, and physiological adaptations of mangrove species. This study aims to observe the survival and growth rate of Rhizhopora mucronata in Peunaga Cut Ujong, Meurebo, West Aceh. The mangroves were planted in 2022 and observed one year after planting. The observation and data collection of 35 tree samples were conducted every two weeks. The results showed a decrease in the survival rate from the third month of observation until the end, showing a decrease of 78%. In contrast, tree growth increased from months 1 to 5. Salinity conditions and substrates dominated by sand with minimal nutrients indicate adaptation to the growth of some relatively small mangrove species. Fluctuating salinity conditions with the dominance of sand have the potential to support the survival of R. mucronata, although with low growth. Its main influence still needs to be studied over a longer period. Keywords: adaptations, growth, morphometrics, salinity